The multiple dimensions of institutional complexity in international business research - Verbeke, Alain; Tulder, Rob van; Rose, Elizabeth Louise; Wei, Yingqi, 1974- (Emerald Publishing Limited, 2021)
'The Multiple Dimensions of Institutional Complexity in International Business Research' provides a fresh overview of many novel international business research challenges as they pertain to salient institutional dimensions with a locational component. The first part of the Volume includes chapters honoring the work of Eleanor Westney. These chapters address subject matter related to globalization challenges in the realm of the 'new normal' of populism and de-globalization tendencies. They focus on how the 'new normal', as well as various rapidly evolving institutions, will affect the functioning of multinational enterprises. The subsequent parts explore the impacts on international business of home country institutions; host country institutions; cross-country and subnational institutions; and finally, sustainability pressures. The book is strongly focused on the multiple contemporary dimensions of institutions and how they affect internationally operating firms. It is a must read for scholars and postgraduate students interested in the 'new normal' on a global scale.
Includes index.
Keywords: International business enterprises -- Management -- Research.; Communication in management.; Business & Economics -- International -- General.; International business.; elektronické knihy; electronic books